Starch-based polymeric materials and nanocomposites chemistry, processing, and applications - Ahmed, Jasim (CRC Press, 2012)
"Preface Biodegradable polymers from renewable resources have attracted much attention in recent years. Starch has been considered as one of the most promising candidates among biopolymers mainly because of its attractive combination of availability and price. Starch is unique in its application and versatility. In addition to its contribution to processing industries, research on starch is currently more focused on the development of biodegradable packaging materials and the synthesis of starch derivatives, bionanoparticles, and bionanocomposites. In order to extend applications of starch as primary packaging materials, current research has focused on starch blends, especially starch/polyester (e.g., polylactides [PLA], polycaprolactone [PCL], and polybutylene succinate [PBS]) biodegradable blends. However, starch/polyester are not compatible for blending and, therefore, a reactive compatibilization process known as reactive extrusion is used to synthesize starch/polyester blends at high starch levels (>20 wt%). The process can also be expanded to plasticized starch and nanocomposites by incorporating nanoparticles in the blend. Such nanocomposites exhibit improved stiffness and toughness, solvent and UV resistance, gas barrier properties, thermal stability, and flame retardancy as compared to conventional composites. Rheological and mechanical properties during plasticization and nanocomposite formation provide a better understanding of structural modification and degree of dispersions of nanoparticles into biopolymers"-- Provided by publisher.
Keywords: Biodegradable plastics.; Biopolymers.; Nanocomposites (Materials); elektronické knihy; electronic books